Husband's smoking status and breast cancer risk in Japan: From the Takayama study. Issue 4 (9th March 2015) - Wada, Keiko; Kawachi, Toshiaki; Hori, Akihiro; Takeyama, Naoharu; Tanabashi, Shinobu; Matsushita, Shogen; Tokimitsu, Naoki; Nagata, Chisato
Abstract : The effects of smoking on breast cancer remain unclear. We assessed the associations of subjects' or husbands' smoking status with breast cancer incidence in a population‐based prospective study in Japan. The subjects were 15 719 women aged 35 years or older. The follow up was conducted from September 1992 to March 2008. Cancer incidence was mainly confirmed through regional population‐based cancer registries. Breast cancer was defined as code C50 according to the International Classification of Diseases and Health Related Problems, 10th Revision. Lifestyle, including smoking status, was assessed with a self‐administered questionnaire. Alcohol consumption was assessed with a validated food‐frequency questionnaire. After multivariate adjustments for age, body mass index, alcohol consumption, physical activity, education, age at menarche, age at first delivery, menopausal status, number of children and history of hormone replacement therapy, active smoking was not associated with the risk of breast cancer. Compared with never smokers whose husband had never smoked, the risks of breast cancer were 1.98 (95% CI: 1.03–3.84) among never smokers whose husband was a current smoker of 21 cigarettes per day or more. The increased risk of breast cancer among women having a smoking husband was pronounced among those who did not habitually consume alcohol. These results suggest that exposure to smoke from husbands is a potential risk factor for breast cancer. The impact of alcohol consumption on the increased breast cancer risk from passive smoking needs to be addressed in further studies. Abstract : A prospective Japanese cohort study demonstrated the association between exposure to secondhand cigarette smoke from husband and increased risk of breast cancer, with a dose‐response relationship, especially for non‐drinkers. Passive smoking should be consistently considered as a risk factor for breast cancer. The modifying effects of alcohol on increased breast cancer risk from passive smoking need to be confirmed in further studies.